P397 Autologous stem cell transplantation in refractory Crohn's disease: evaluation of a modified mobilisation regimen and analyses of the cost-effectiveness. (25th January 2019) - Mahmmod, N; Mahmmod, S; Severs, M; Koene, H; van Wijk, F; Oldenburg, B; Fidder, H
Abstract: Background: Autologous stem cell transplantation (ASCT) is a last resort treatment in patients with refractory Crohn's disease (CD), but is associated with high costs and considerable toxicity. In this study, we evaluate the impact of a modified mobilisation regimen on toxicity, efficacy and costs. Methods: In this prospective observational study, adult patients with refractory CD were included between 2014 and 2017 from six University Medical Centres. We eliminated cyclophosphamide from the mobilisation regimen to limit toxicity. The aims of this study were to assess the sustained remission at 1 year (clinical remission (CDAI < 150) AND no use of immunosuppressives or biologicals AND no endoscopic or radiologic evidence of active disease), the clinical benefit (CDAI < 150 or a significant decrease of 100 points), toxicity, cost effectiveness and quality of life (QoL). Results: Eight patients (5 females, median age 49 years, range 40–67 years) underwent ASCT. Seven patients completed a follow-up of 52 weeks. None of the patients reached the combined primary endpoint at Week 52. However, 3/5 (60%) patients reached clinical remission defined as CDAI < 150, and a fourth had a significant decrease of 100 points in the CDAI (clinical benefit in 4/6 patients). The CDAI was not assessed in two patients, because of the presence of an endostomy. In 2/6 patients no radiologic and in another 2/6 no endoscopic disease activity was observed at Week 52. In 4/7 patients QoL significantly increased (IBDQ increase of >16 points, range 28–49 points). All patients were discharged from the hospital within 4 weeks after ASCT. In total, 35 adverse events were reported of which 8 were considered serious. Analysis of the healthcare costs (1 year before vs. 1 year after ASCT) of the first 4 patients shows a substantial reduction in the costs. Adverse events per patient Healthcare costs Conclusions: Although the combined primary endpoint was not reached, we observed clinical benefit in more than half of the patients with refractory CD treated with ASCT. The use of a less toxic regimen for the mobilisation may lead to a substantial reduction in the incidence of adverse events without impacting efficacy. ASCT may lead to a considerable decrease in the healthcare costs.